The state, the law, and the people in the Roman empire / Brian Campbell, Professor Emeritus, the Queen's University of Belfast. - Campbell, J. B. (Cambridge University Press, 2025)
This volume makes more widely available to students and teachers the treasure trove of evidence for the administrative, social, and economic history of Rome contained in the Digest and Codex of Justinian. What happened when people encountered the government exercising legal jurisdiction through governors, magistrates, and officials within the legal framework and laws sponsored by the state? How were the urban environment of Rome and Italy, the state's assets, and human relations managed? How did the mechanisms of control in the provinces affect local life and legal processes? How were contracts devised and enforced? How did banks operate? What was the experience of going to court like, and how did you deal with assault or insult or recover loss? How did you rent a farm or an apartment and protect ownership? The emperor loomed over everything, being the last resort in moderating relations between state and subject.